Water Conservation and Management Practices at the University of Sharjah to Achieve Sustainability Excellence - Siddique, Mohsin; Semerjian, Lucy; Bettayeb, Maamar; A. Al-Sadoon, Zaid; Al Jaberi, Bushra Hussein; Eltarabishi, Fatma; AlSane, Shahd Ibrahim (Journal of Sustainability Perspectives, 2021)
The University of Sharjah is a leading educational and research institution in the Gulf region. To stimulate the different aspects of sustainability in education and research as well as to ensure the implementation of sustainability concepts throughout the University campus operations, the concept of sustainability circles is implemented. The University being in hot-arid-zone and mostly surrounded by desert terrain relies on unconventional water conservation programs and initiatives such as the use of innovation & technology, reuse and recycling of water, and awareness campaigns. In line with such programs, the use of potable water is limited for hygiene purposes and wastewater generated within the University is reused after treatment to irrigate the vast green spaces through the most efficient irrigation water application systems. Examples of water conservation practices include use of efficient water devices, reuse of treated greywater for toilet flushing at a selected location, water quality monitoring, preservation to conserve water for its intended use, promoting waterless car wash on the campus grounds etc. On-campus water is also conserved through disseminating knowledge and awareness to the University community and beyond through various sustainability related programs and initiatives organized by Sustainability Office for water conservation and environmental protection.